(untitled) - Friedman, Avi (Hoboken, N.J., 2005)
Homes Within Reach provides the first systematic guide for planning, designing, and constructing modest, yet high-quality, homes. From siting and foundations to systems, layouts, and interior and exterior finishes, it covers dozens of design and construction techniques that promote housing quality with sensitivity to lowering costs.
Keywords: Housing,Low-income housing,Architecture, Domestic,House construction,Nhà ở,Nhà ở thu nhập thấp,Kiến trúc, trong nước,Xây dựng Nhà; Planning,Cost effectiveness,Kế hoạch,Chi phí hiệu quả